Internal control system of the public sector: a study in the counties of the Caí Valley - RS (Revista Brasileira de Contabilidade e Gestão, 2019)
The objective of this research is to analyze how the operation and the structure of Internal Control Systems of the counties of the Caí Valley - RS. In methodological terms this research is classified as qualitative and quantitative, descriptive and survey. As result of the study, positives and negatives points of the units were pointed out. The main negatives points were the formation of servers with only secondary education, the absence or segregation of the activities of accountants in the Central Units of Internal Control, the hours worked and insufficient training. The positives points are the experience of the servers in the public area, the formalization and registration of the works and the composition of the units by effective servers. It is believed these analysis may help the decision-making of public managers in the improvement of their controls, contributing for the society in general, mainly for the most deprived segments which practically depend on the services provided by public administration.
Keywords: Internal Control System; Public Administration; Central Internal Control Unit; Internal Control